Pengaruh Penambahan Ekstrak Kunyit (Curcuma domestica) dengan Konsentrasi yang Berbeda Terhadap Daya Simpan dan Uji Organoleptik Abon Daging Itik - ., Jauhar Habibah; ., Rizky Febriyani Putri; ., Maya Istyadji (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Duck meat is one of the livestock potentials that has economic value and is a source of high quality protein. Duck meat processing needs to be done to add flavor and improve quality so that it has a longer shelf life. The addition of turmeric in meat processing can be used as a spice and natural antioxidant. The purpose of this study was to determine the effect of adding turmeric extract on the results of water content and pH levels as well as organoleptic tests on processed shredded duck meat. The method used in this study was an experimental method with a completely randomized design (CRD) experiment with the addition of 0%, 5%, 10%, and 15% turmeric extract. Storage time was 30 days at room temperature and 3 repetitions were carried out for each treatment. The results showed that there was an effect of adding turmeric extract on water content (p=0.000) and pH level (p=0.016). The results of the organoleptic test analysis of shredded duck meat showed that there was an effect of adding turmeric extract on the color and texture of shredded duck meat. Based on the de Garmo effectiveness test, the P2 treatment (10%) was the best and most preferred treatment by the panelists with a relative value of 0.75.